The fragile X syndrome. - Hirst, M; Knight, S; Bell, M; Super, M; Davies, K (1992)
An amplification of a highly unstable DNA element has been identified at the fragile X locus in Xq27.3. This sequence appears to be both the source of the primary mutation causing the fragile X syndrome, apparently having its causative effect through the methylation of the FMR-1 HTF island and the region of cytogenetic fragility. The direct analysis of the genotype of carrier and affected individuals can be used as a direct diagnosis tool which will improve both the accuracy and speed of diagnosis. The identification of hereditary unstable DNA in a disease with such a wide level of non-penetrance and variable phenotype may give clues as to the basis of non-penetrance in other human genetic disorders.